Analisis Penerapan Sistem Informasi Akuntansi Dalam Pengelolaan Data Keuangan Dan Operasional Pada PT.Seafood Inspection Laboratory - Dewa Ayu Winda Sapitri; Ni Wayan Alit Erlina Wati; I Made Endra Lesmana Putra (UNHI Press, 2026)
This study aims to analyze the implementation of Accounting Information Systems (AIS) in managing financial and operational data at PT. Seafood Inspection Laboratory. This research is motivated by the importance of system integration in supporting the effectiveness and efficiency of company data management, as well as the existing issue of suboptimal implementation of Enterprise Resource Planning (ERP)-based systems using SAP across all divisions. This study employs a qualitative approach with a case study research design. The informants in this study consisted of 8 individuals, including the finance manager, accounting staff, operational manager, and logistics staff, selected using purposive sampling technique. Data collection methods were conducted through in-depth interviews, observations, and documentation. The data analysis technique used was the interactive model of Miles and Huberman, which includes data reduction, data display, and conclusion drawing. The results indicate that the implementation of SAP has a positive impact on financial data management, particularly in improving the accuracy, timeliness, and organization of financial reports. However, the system has not been fully integrated across all divisions, especially in the logistics department, which still relies on spreadsheets, leading to duplicate data entry and potential recording errors. Other challenges include limited user understanding and lack of training in system usage. Therefore, optimization efforts are needed through system integration, human resource training, and stronger management support to enhance the overall effectiveness of AIS. This study is expected to contribute to companies in improving the quality of financial and operational data management through integrated information systems. Furthermore, it can serve as a reference for future research related to the implementation of ERP-based Accounting Information Systems.